Comparative Renewables Policy Political, Organizational and European Fields - Boasson, Elin Lerum; Leiren, Merethe Dotterud; Wettestad, Jørgen (Routledge Studies on the Governance of Sustainability in Europe, 2021)
Challenging one-eyed technology-focused accounts of renewables policy, this book provides a ground-breaking, deep-diving and genre-crossing longitudinal study of policy development. The book develops a multi-field explanatory approach, capturing inter-relationships between actors often analyzed in isolation. It provides empirically rich and systematically conducted comparative case studies on the political dynamics of the ongoing energy transition in six European countries. While France, Germany, Poland and the United Kingdom opted for 'technology-specific' renewables support mixes, Norway and Sweden embarked on 'technology-neutral' support mixes. Differences between the two groups result from variations in domestic political and organizational fields, but developments over time in the European environment also spurred variation. These findings challenge more simplistic and static accounts of Europeanization. This volume will be of key interest to scholars and students of energy transitions, comparative climate politics, policy theory, Europeanization, European integration and comparative European politics more broadly, as well practitioners with an interest in renewable energy and climate transition. The Open Access version of this book, available at: https://www.taylorfrancis.com/books/e/9780429198144, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.